Unusual spectroscopic and electrochemical properties of the 2[4Fe-4S] ferredoxin of Thauera aromatica. - Boll, M; Fuchs, G; Tilley, G; Armstrong, F; Lowe, D (2000)
A reduced ferredoxin serves as the natural electron donor for key enzymes of the anaerobic aromatic metabolism in the denitrifying bacterium Thauera aromatica. It contains two [4Fe-4S] clusters and belongs to the Chromatium vinosum type of ferredoxins (CvFd) which differ from the "clostridial" type by a six-amino acid insertion between two successive cysteines and a C-terminal alpha-helical amino acid extension. The electrochemical and electron paramagnetic resonance (EPR) spectroscopic properties of both [4Fe-4S] clusters from T. aromatica ferredoxin have been investigated using cyclic voltammetry and multifrequency EPR. Results obtained from cyclic voltammetry revealed the presence of two redox transitions at -431 and -587 mV versus SHE. X-band EPR spectra recorded at potentials where only one cluster was reduced (greater than -500 mV) indicated the presence of a spin mixture of S = (3)/(2) and (5)/(2) spin states of one reduced [4Fe-4S] cluster. No typical S = (1)/(2) EPR signals were observed. At lower potentials (less than -500 mV), the more negative [4Fe-4S] cluster displayed Q-, X-, and S-band EPR spectra at 20 K which were typical of a single S = (1)/(2) low-spin [4Fe-4S] cluster with a g(av) of 1.94. However, when the temperature was decreased stepwise to 4 K, a magnetic interaction between the two clusters gradually became observable as a temperature-dependent splitting of both the S = (1)/(2) and S = (5)/(2) EPR signals. At potentials where both clusters were reduced, additional low-field EPR signals were observed which can only be assigned to spin states with spins of >(5)/(2). The results that were obtained establish that the common typical amino acid sequence features of CvFd-type ferredoxins determine the unusual electrochemical properties of the [4Fe-4S] clusters. The observation of different spin states in T. aromatica ferredoxin is novel among CvFd-type ferredoxins.